2014
DOI: 10.1371/journal.pone.0107480
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary and Cardiac Function in Asymptomatic Obese Subjects and Changes following a Structured Weight Reduction Program: A Prospective Observational Study

Abstract: BackgroundThe prevalence of obesity is rising. Obesity can lead to cardiovascular and ventilatory complications through multiple mechanisms. Cardiac and pulmonary function in asymptomatic subjects and the effect of structured dietary programs on cardiac and pulmonary function is unclear.ObjectiveTo determine lung and cardiac function in asymptomatic obese adults and to evaluate whether weight loss positively affects functional parameters.MethodsWe prospectively evaluated bodyplethysmographic and echocardiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
1
3
0
1
Order By: Relevance
“…Although at baseline respiratory flows and volumes were substantially within normal limits, 6 months after SG, the unchanged Tiffeneau index in the presence of increased dynamic pulmonary parameters (FVC and FEV 1 ) suggests a major impact of weight loss on restrictive components of ventilation. Analysing the pulmonary flows at different forced expiration levels and in accordance with the findings of Held et al, a more pronounced improvement was observed for small airways (MEF 25 ), compared with the pulmonary flows in larger airways (MEF 50 and MEF 75 ) [25]. Rubstein et al stated that obesity carries flow limitations that could be explained, among other mechanisms, by a state of systemic inflammation and an increase in pulmonary blood volume, which lead to congestion of vessels and a reduction in the size of small airways [4,26].…”
Section: Pulmonary Function At Restsupporting
confidence: 85%
“…Although at baseline respiratory flows and volumes were substantially within normal limits, 6 months after SG, the unchanged Tiffeneau index in the presence of increased dynamic pulmonary parameters (FVC and FEV 1 ) suggests a major impact of weight loss on restrictive components of ventilation. Analysing the pulmonary flows at different forced expiration levels and in accordance with the findings of Held et al, a more pronounced improvement was observed for small airways (MEF 25 ), compared with the pulmonary flows in larger airways (MEF 50 and MEF 75 ) [25]. Rubstein et al stated that obesity carries flow limitations that could be explained, among other mechanisms, by a state of systemic inflammation and an increase in pulmonary blood volume, which lead to congestion of vessels and a reduction in the size of small airways [4,26].…”
Section: Pulmonary Function At Restsupporting
confidence: 85%
“…In addition, previously obese according to BMI, showed lower declines in FEV 1 and FVC than those who were never obese in an 8 years interval between two follow-up [30]. Weight loss whether through hypocaloric diet [36, 37] or surgical interventions [38, 39], was also associated with improvements in pulmonary function tests. In our sample we observed that individuals who were in the highest FMI category only at 18 years, 81.3% among men and 60.2% among women reached the recommendation of at least 150min/week of exercises, percentage beyond the sample mean (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Although our study convincingly related a reduced MEF 50 to clinically relevant outcomes, we acknowledge that the causality of these associations is not stringent. Some studies found that MEF 50 was below average in subgroups of healthy never smokers [ 4 , 5 ], or asymptomatic subjects [ 28 ]. Further, higher body mass index levels may attenuate MEF [ 29 ], but we observed no relation between body mass index levels and low MEF 50 (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%